Options for Controlling Type 2 Diabetes during Ramadan - Almalki, Mussa H.; Alshahrani, Fahad (Frontiers in Endocrinology, 2016)
The Muslim population is about 1.5 billion worldwide. Based on a global diabetes prevalence of 4.6%, it is estimated that there are about 50 million Muslims with diabetes around the world who observe fasting during the month of Ramadan each year. Ramadan, one of the five pillars of Islam, and which takes place during the ninth month of the Islamic calendar, involves fasting from sunrise to sunset. During the fast, Muslims are required to refrain from eating food, drinking, using medications, and smoking from dawn until after sunset, with no restrictions on food or fluid intake between sunset and dawn. Islam exempts people from the duty of fasting if they are sick, or if fasting may affect their health, as fasting for patients with diabetes carries a risk of an assortment of complications, including hypoglycemia, postprandial hyperglycemia, and metabolic complications, associated with dehydration. Nevertheless, a large number of people with diabetes who still choose to fast during Ramadan despite the advice of their doctor, and the permission received from religious authorities thus create medical challenges for themselves and their health-care providers. It is thus important for patients with diabetes who wish to fast during Ramadan to make the necessary preparations to engage in fasting as safely as possible. This review presents a guide to the care of diabetic patients during Ramadan to help them fast safely if they wish to do so.